Discursive Power and the Internationalization of Universities in British Columbia and Ontario - King, Conrad (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2020)
Universities rationalize internationalization according to paradigms that emerge from different contexts. With the advent of internationalization strategies by federal and provincial governments, what effect do government ideas have on Canadian universities? This article evaluates the discursive power of government, and its role in discourse communities pertaining to higher education internationalization. Employing a discursive institutionalist framework and qualitative research design, I evaluated discursive content at 16 Tier 1 and 2 universities in British Columbia and Ontario. The findings indicate that governments have had weak ideational influence over the past decade, especially at universities with a global or nationalorientation. Many of these universities have been undergoing a subtle shift in their internationalization rationales—although not all, and not at the same pace. Yet some Canadian universities have increasingly “looked within” to rationalize internationalization, because their discourse communities are dominated by internal voices more concerned with organizational context than global competitiveness.